The special successor in Iraqi civil law - Ari Farooq Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In general, the contract has no effect except its parties who contributed to its conclusion, and it does not extend to third parties. From here begins the relativity of the effects of the contract in terms of persons, which is the general rule in this regard. However, the Iraqi legislator and comparative legislation explicitly stipulate that the effects of the contract apply under certain conditions against those who were not a party to it and did not voluntarily contribute to its creation. Rather, he receives from one of the parties to the specific contract a specific thing or right. So we are faced with the holder of a legal position called in legal terminology as (the special successor), and the effects of that contract extend to this successor as if he were a party to it, because of the relationship that exists between the special successor and his (predecessor), who is the original party in the contract whose effect extends to the successor. The special and this relationship is (the special successor), and although the Iraqi legislator and comparative legislation have acknowledged the transfer of the effect of the predecessor’s contract to the special successor under certain conditions, the concept of the special successor was not clarified, which led to the ambiguity of the meaning of the special successor, and the role of jurisprudence is also not As much as it is necessary to explain the concept of the special successor, I will limit myself in this field to a few attempts that are not commensurate with the importance of this topic, and even those attempts were in conflict with each other, and since the rights of the special successor are not immune from the damages he faces from the side of the predecessor, or from the side of (third parties). The one who concluded the contract with the predecessor and its effect goes to the special successor, so the special successor needs protection.